PENGARUH NOM, CAR, NPF NETT DAN FDR TERHADAP KINERJA KEUANGAN PADA BCA SYARIAH PERIODE 2013-2022: THE INFLUENCE OF NOM, CAR, NPF NETT AND FDR ON FINANCIAL PERFORMANCE IN BCA SYARIAH FOR THE PERIOD 2013-2022 - Aris, Riyanti A; Eki Tiyas Nurulia; Noorikha Pandayahesti Saputeri (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
This study aims to analyze the effect of NOM, CAR NPF NETT and FDR on financial performance at BCA Syariah for the period 2013-2022. Bank financial performance is a description of the financial condition over a certain period of time including aspects of fund collection and distribution to evaluate bank financial performance using various variables. This description is usually presented in the annual financial report. This study uses a descriptive quantitative approach method with secondary data analysis, namely research that uses numerical/numerical data. which is obtained in the annual financial report that has been published by BCA Syariah. By using descriptive statistical techniques, classical assumptions, multiple regression hypothesis testing, coefficient of determination. Partial test and normality test Based on the simultaneous test of the F test that has been carried out, the regression coefficient F count is 463.657 F table of 2.47 so that H0 is rejected and Ha is accepted with a significance of 0.000 0.05 (which has been set), it can be concluded that simultaneously there is a significant effect between the independent variables NOM, CAR, NPF NETT and FDR on financial performance (ROA). partial research results: NOM has a significant effect on financial performance or ROA, CAR has no effect on financial performance or ROA. NPF NETT shows an effect on financial performance or ROA, FDR has no effect on financial performance or ROA.